Preventing injuries in alpine skiing giant slalom by shortening the vertical distance between the gates rather than increasing the horizontal gate offset to control speed - Gilgien, M.; Crivelli, P.; Kröll, J.; Luteberget, L. S.; Müller, E.; Spörri, J. (British Journal of Sports Medicine, 2020)
Background/Aim: To set a safe giant slalom course, speed needs to be controlled in certain sections. Speed may be reduced by adjusting how the gates are set on a course. We studied the effect of elements of course-setting, entrance speed and terrain incline on the mechanics of turning (ie, turn speed, turn radius, and ground reaction force and impulse).